Tìm x biết
\(\sqrt{x+2}\) =\(\frac{5}{7}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1.
= -(13 + 3 căn7 ) / 2 + -(7 + 3 căn7 ) / 2
= -7 + 3 căn7
\(\frac{x}{16}=\frac{2\sqrt{27+7\sqrt{5}}}{\sqrt{10}+7\sqrt{2}}\)
\(\Leftrightarrow\frac{x}{16}=\frac{\sqrt{54+14\sqrt{5}}}{\sqrt{5}+7}\)
\(\Leftrightarrow\frac{x}{16}=\frac{\sqrt{49+2.7.\sqrt{5}+5}}{\sqrt{5}+7}\)
\(\Leftrightarrow\frac{x}{16}=\frac{\sqrt{\left(\sqrt{5}+7\right)^2}}{\sqrt{5}+7}=\frac{\sqrt{5}+7}{\sqrt{5}+7}=1\)
\(\Leftrightarrow x=16\)
\(đk:x\ge-2\)
\(\sqrt{x+2}=\frac{5}{7}\Leftrightarrow x+2=\frac{25}{49}\Leftrightarrow x=\frac{25}{49}-2=\frac{-73}{49}\left(n\right)\)
vậy \(x=\frac{-73}{49}\)
\(\sqrt{x+2}=\frac{5}{7}\)
\(\Rightarrow x+2=\frac{25}{49}\)
\(\Rightarrow x=\frac{25}{49}-2\)
\(\Rightarrow x=\frac{-73}{49}\)
Vậy, \(x=\frac{-73}{49}\)
\(\sqrt{x+2}\) = \(\frac{5}{7}\)
\(\Rightarrow\) x + 2 = \(\left(\frac{5}{7}\right)^2\)
\(\Rightarrow\) x + 2 = \(\frac{25}{49}\)
\(\Rightarrow\) x = \(\frac{25}{49}\) - 2
\(\Rightarrow\) x = \(\frac{-73}{49}\)
Vậy x = \(\frac{-73}{49}\)
\(\sqrt{x+2}=\frac{5}{7}\)
\(\Rightarrow x+2=\left(\frac{5}{7}\right)^2\)
\(\Rightarrow x+2=\frac{25}{49}\)
\(x=\frac{25}{49}-2=-\frac{73}{49}\)